Tranexamic acid to reduce blood loss in women at high risk of postpartum hemorrhage undergoing cesarean delivery-a randomized controlled trialAJOG Global Reports at a Glance - Bethany G. Neumann, MD; Mrityunjay C. Metgud, MD; Matthew K. Hoffman, MD, MPH; Kamal Patil, MD; Mahadevi Savanur, MD; Vinutha Hanji, MD; Madiwalayya S. Ganachari, MD; Manjunath Somannavar, MD; Shivaprasad S. Goudar, MD, MPH (Elsevier, 2024)
BACKGROUND: Postpartum hemorrhage is a leading cause of maternal morbidity and mortality. Tranexamic acid has proven to be useful in treating hemorrhage from acute blood loss. However, its role in preventing blood loss in women at high risk of postpartum hemorrhage undergoing cesarean delivery is not well studied. OBJECTIVE: This study aimed to assess the role of tranexamic acid in reducing blood loss during elective and unscheduled cesarean deliveries in women at high risk of postpartum hemorrhage. STUDY DESIGN: This was a prospective, placebo-controlled, randomized controlled trial from March 2021 to February 2022 at the Karnatak Lingayat Education Society Dr. Prabhakar Kore Hospital and Medical Research Centre, Belagavi, India. Women at a high risk of postpartum hemorrhage undergoing cesarean delivery were recruited and randomized to receive either tranexamic acid or placebo (1:1) at least 10 minutes before skin incision. High-risk factors for postpartum hemorrhage included obesity, hypertension, multiparity, previous cesarean delivery, multiple pregnancy, abnormally implanted placenta, placenta previa, abruption, uterine leiomyomas, polyhydramnios, and fetal macrosomia. The primary outcome was blood loss, calculated by a formula using pre- and postoperative hematocrit levels. In addition, gravimetrically measured blood loss was measured and compared between the 2 groups. RESULTS: A total of 212 women met the inclusion criteria and were randomized (tranexamic acid [n=106] and placebo [n=106]). The mean blood loss estimates were 400.9 mL in the tranexamic acid group and 597.9 mL in the placebo group (P<.001). The mean gravimetrically measured blood loss estimates were 379.2 mL in the tranexamic acid group and 431.1 mL in the placebo group (P<.001). In addition, there was a significant difference in the fall in hemoglobin levels (1.04 vs 1.61 g/dL) and change in hematocrit levels (3.20% vs 4.95%) from the pre- to postoperative period between the 2 groups (P<.001). No difference in the need for additional uterotonics (P=.26) or the need for postoperative parental iron (P=.18) was noted. No woman was transfused in either group. CONCLUSION: High-risk women receiving tranexamic acid had significantly less blood loss than women receiving placebo during cesarean delivery.